2016
DOI: 10.1088/1367-2630/18/10/103047
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rotation detection by Coriolis force measurement using optomechanics

Abstract: In this article, we present an application of the optomechanical cavities for absolute rotation detection. Two optomechanical cavities, one in each arm, are placed in a Michelson interferometer. The interferometer is placed on a rotating table and is moved with a uniform velocity ofȳ with respect to the rotating table. The Coriolis force acting on the interferometer changes the length of the optomechanical cavity in one arm, while the length of the optomechanical cavity in the other arm is not changed. The pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
(106 reference statements)
0
27
0
Order By: Relevance
“…We propose an application of two-dimensional optomechanical oscillator as a gyroscope to detect absolute rotation. We showed that the two-dimensional optomechanical gyroscope's sensitivity is better than onedimensional optomechanical gyroscope [15] by a factor of g w m m . Using the parameters from [36], the sensitivity of the gyroscope is estimated as 7×10 −15 rad s -1 -/ Hz 1 2 at 0 K temperature.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…We propose an application of two-dimensional optomechanical oscillator as a gyroscope to detect absolute rotation. We showed that the two-dimensional optomechanical gyroscope's sensitivity is better than onedimensional optomechanical gyroscope [15] by a factor of g w m m . Using the parameters from [36], the sensitivity of the gyroscope is estimated as 7×10 −15 rad s -1 -/ Hz 1 2 at 0 K temperature.…”
Section: Resultsmentioning
confidence: 87%
“…At I l =I o , we get the best sensitivity which corresponds to the lowest point in the Purple curve. Minimizing equation ( (20) is in the same order of magnitude as the sensitivity achieved in the squeezed-vacuum gyroscope [15]. In the squeezed-vacuum gyroscope, squeezed vacuum field is injected in to two optomechanical cavities to suppress the shot noise and back-action noise and thus improving the sensitivity of the gyroscope.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations